Ibn Sina’s Biopsychosocial Balance: Insights for Mental Health Preservation and Islamic Psychology - Jarman Arroisi; Syamsuddin Arif; Muhammad Alif Rahmadi (Journal of Islamic Thought and Civilization, 2024)
Historically, the discourse surrounding mental health within the framework of intellectual traditions has held profound significance, reflecting this issue's enduring relevance and complexity. The contribution of the leading scholar in Islamic Psychology, Ali Bin Abdullah Ibnu Sina, deserves high recognition for his conceptual significance and practical impact concerning mental health and the Islamic perspective. Therefore, this research aims to reveal Ibn Sina's thoughts and ideas regarding the theory of balance between mental health and its impact on overall physical, cognitive, social, and emotional well-being. For this purpose, the qualitative research methodology was deployed using descriptive analysis methods. The study found several pivotal results; firstly, in his corpus, Avicenna's theory has had a long-term impact on theoretical contributions to biopsychosocial health and well-being. Secondly, his ideas prioritize balance or I'tidal, which includes life balance, dietary recommendations, lifestyle adjustments, the balance of body humour, and psychological well-being, and elements that are significant for preserving mental stability. Lastly, his theory of I'tidal aims to serve as a foundational paradigm for the integrated analysis of psychological and biological medicine, focusing significantly on the psychological state continuance of the individual.